Physiological Response of Thallasia hemprichii on Antrophogenic Pressure In Pari Island, Seribu Islands, DKI Jakarta - Aditya Hikmat Nugraha; Dietriech G. Bengen; Mujizat Kawaroe (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2017)
Seagrass ecosystem is one of tropical marine ecosystem and have important function. The function of ecosystem like a feeding and nursery ground for marine biota. Antrophogenic pressure is one of threat for seagrass ecosystem sustainability. This research study about effect antropogenic pressure for seagrass Thallasia hemprichii physiology response in some different location at Great Barrier Pari Island. The physiology response study cover growth, heavy metal bioaccumulation and histology analysis. The result shows that growth of leaf and rhizome Thalassia hemprichii have positif correlation with nutrient consentration in environment. The highest growth of leaf Thalassia hemprichii at 2nd station (4.16 mm.day-1) and the highest growth of rhizome Thalassia hemprichii at 4th station (1.3 mm.day-1). Seagrass can accumulation heavy metal from environment. The highest heavy metal accumulation is Pb. Not correlation between heavy metal consentration in seagrass with heavy metal concentration from environment. Analysis histology result that not damage seagrass tissue in all research station. Keyword : Bioacumulation,Growth,Physiology,Seagrass, Thalassia hemprichiiSeagrass ecosystems is one of the tropical marine ecosystems that have important functions, among others as a feeding and nursery ground for marine life. Anthropogenic stress is one of the threats that may inhibit the survival of seagrass ecosystems. This study examines the effects of anthropogenic pressures on physiological responses of seagrass Thalassia hemprichii at several different locations in Pari Islands. Physiological responses studied were leaves and rhizome growth, bioaccumulation of heavy metals and histological tissue analysis on seagrass. The results showed that the growth response of seagrass has a positive correlation with the nutrients in the environment. Seagrass leaf growth is highest at Station 2 (4.16 mm.day-1) and rhizome growth is highest at Station 4 (1.3 mm.day-1). Seagrass accumulate heavy metals from the environment and accumulation of heavy metals is highest on Pb. There is no correlation between the concentration of heavy metals in the seagrass and environment. The results of histological analysis showed that there was no damage to the tissue of seagrass leaf and rhizome. Keywords : Bio-acumulation, Growth, Physiology, Seagrass, Thalassia hemprichii